Impact of tactile dysfunction on upper-limb motor performance in children with unilateral cerebral palsy - Auld, M.; Boyd, Roslyn; Moseley, G.; Ware, R.; Johnston, L. (2012)
Impact of tactile dysfunction on upper-limb motor performance in children with unilateral cerebral palsy. Objective: To determine the relationship between tactile function and upper-limb function in children with unilateral cerebral palsy (CP). Design: Cross-sectional study. Setting: Assessments were performed in community or hospital venues or in participants' homes. Participants: Recruitment information was sent to 253 possible participants with unilateral CP (aged 818y), and N=52 participated (median age [interquartile range], 12y [914y]; Gross Motor Functional Classification System level I=34; II=18; Manual Abilities Classification Scale level I=36; II=16). Interventions: Not applicable. Main Outcome Measures: Tactile assessment included 1 test of registration, 5 tests for spatial perception, and 1 test for texture perception. Upper-limb motor function was assessed using 2 unimanual tests, the Melbourne Unilateral Upper Limb Assessment (MUUL) and Jebsen-Taylor Test of Hand Function (JTTHF), and 1 bimanual test, the Assisting Hand Assessment (AHA). Results: Tactile registration and all tests of spatial perception were moderately related to the MUUL, JTTHF, and AHA (P<.001). Texture perception was not related to upper-limb motor function. Regression analysis showed that single point localization, a unilateral tactile spatial perception test, contributed most strongly to unimanual capacity (29% explained variance in MUUL and 26% explained variance in JTTHF), whereas double simultaneous, a bilateral tactile spatial perception test, contributed most strongly to bimanual performance (33% for the AHA). Conclusions: Spatial tactile deficits account for approximately 30% of the variance in upper-limb motor function in children with unilateral CP. This emphasizes the need for routine tactile assessment and targeted treatment of tactile spatial deficits in this population. © 2012 by the American Congress of Rehabilitation Medicine.